Cultural Transformation in Customers’ Purchasing: Is It Affected by Effective Social Media Marketing Activities? - Kussoy, Renata (Lembaga Penelitian Universitas Pasundan, 2023)
Nowadays we can clearly see the transformation and the shift of many customers in purchasing the products they need. From traditional way of shopping by visiting malls or traditional markets to online purchasing. This research is to study the impact of social media marketing on customers’ intention to purchase the products, and the mediating effects of consumers’ engagement in relation between digital marketing and purchase intention. Using mixed method in a case study of one baby fashion X shop in Bandung, the writer obtained the data from digital application (Shopee) to see the total amount of purchase per month for the last 18 months, questionnaires to receive data of customers’ intention to purchase the products, interview with social marketing designer to know how she designed the platform of its shop production, and the manager marketing to find how he planned his strategies in selling his products in online market. The results show that the social media marketing activities need to be supported by advertising of the products to make it more effective in affecting customers’ engagement in the brand awareness and intention to buy, thus the manager’s strategy should improve his strategic phase, in which he has formal process to plan and execute social media marketing activities with clearly defined objectives and metrics.